The role of social media usage, gratitude, self- esteem, and religiosity on volunteerism among Malaysian youth - Ma’rof, Aini Azeqa; Abdullah, Haslinda; H. Hamsan, Hanina (HRMARS, 2024)
This study investigates the relationship between social media usage, gratitude, self-esteem, religiosity, and volunteerism among Malaysian youth. The research examines how these key factors—social media usage, gratitude, self-esteem, and religiosity—affect youth engagement in volunteer activities. A sample of 419 Malaysian youths was analyzed using quantitative methods, including correlation and regression analyses. The results indicate that gratitude is the strongest predictor of volunteerism, followed by self-esteem, religiosity, and social media usage. Higher levels of gratitude and self-esteem were significantly associated with increased volunteer engagement. These findings highlight the pivotal role of gratitude and self-esteem in fostering volunteerism, while also demonstrating the influence of social media and religiosity. The study provides meaningful insights into the interplay between digital, personal, and religious factors that motivate volunteerism and offers practical recommendations for enhancing youth civic engagement in Malaysia.